Analisis Perlakuan Akuntansi Aset Tetap Pada Badan Keuangan Kabupaten Ngawi (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
Fixed Assets are assets that require careful policies and management in their reporting. The company’s overall financial reporting, both in terms of the condition and description of the company, must be in accordance with the policies that have been determined. The author uses Primary Data in the form of an inventory card and makes direct observations of the regional asset and goods management department by participating in asset input activities. The author also aims to determine the treatment of fixed assets and to determine the suitability of accounting for fixed assets according to SAP No.07 at the Ngawi Regency Finance Agency